Development of a Decolonising Framework for Aboriginal and Torres Strait Islander Health Policy Analysis in Australia - Kehoe, Helen; Schütze, Heike; Spurling, Geoffrey; Lovett, Raymond (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
Analysis of policies relevant to Aboriginal and Torres Strait Islander Peoples could help improve health outcomes—a critical challenge in Australia. While there are many health policy analysis frameworks, we did not find one which supported decolonising approaches across stages of the policy cycle. Generic frameworks were not based on decolonising approaches, and so risk perpetuating structural inequalities underpinning health disparities. Aboriginal and Torres Strait Islander specific frameworks articulated ways of working rather than addressing policy stages. We devised a new policy analysis framework by drawing upon Aboriginal and Torres Strait Islander specific and other policy analysis frameworks. The new framework can help critically analyse existing Aboriginal and Torres Strait Islander health policy and guide future policy making.